A Journey of Continuous Commitment to Martial Arts in Alumni Karate Practitioners (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
This study aimed to explore the driving aspects of continuous commitment towards karate among Singaporean alumni karate practitioners by examining three periods of their journey; commitment to early participation, commitment to sport karate participation and commitment to present participation. The research question behind this study was what are the driving aspects of continuous commitment in alumni Karate practitioners based on early participation, sport karate participation and present participation? Semi-structured interviews were conducted with 7 black-belt karate practitioners between the ages of 21 - 26 years old. Each interview was audio-recorded and transcribed verbatim. For data analysis, thematic analysis was employed and themes were identified and categorised into higher order themes. Member-checking was performed to check transcript accuracy and clarify the themes. Four driving aspects surfaced based on the three periods of commitment; Personal competency, personal enjoyment, personal well-being and personal obligations. The study further discussed the driving aspects and underlying themes that drove continuous commitment to Karate. Results of this study could benefit martial arts clubs and relevant organisations in understanding some of the factors behind karate commitment and engagement. The implications may be translated into healthy lifestyle engagement policies by government or policy-making bodies in encouraging active health and lifelong sport participation. Further research on Karate could focus on the influence of overall training time and club affiliation in driving commitment to the martial art.